Extended Reality International Grand Rounds: An Innovative Approach to Medical Education in the Pandemic Era. (23rd June 2022) - Salavitabar, Arash; Popov, Vitaliy; Nelson, Jeremy; Benedict, Michelle D.; Inniss, Donovan A.; Mahajan, Arushi P.; Cohen, Mark S.; Owens, Sonal T.
Abstract : Problem: While bedside training has always presented its own unique challenges, the COVID-19 pandemic era has intensified barriers to suitable provider and trainee experiences for both patient care and medical education. Approach: This project introduced an innovative solution with the Extended Reality International Grand Rounds, a collaboration between the University of Michigan Center for Medical and Surgical Extended Reality and Imperial College London. Three complex cases were presented to trainees through a wireless, extended reality (XR) headset and augmented by holographic visual aids and expert commentary. This pilot rounding experience was performed through the first-person view of one clinician at the bedside. Outcomes: In 2020, 140 attendees participated in XR International Grand Rounds, and 82 (59%) and 61 (44%) completed pre- and postsurveys, respectively. Survey analysis showed that the majority of respondents (65, 79.3%) had very little to no baseline experience with XR technologies and nearly all (75, 91.5%) agreed that the development and implementation of XR curricula are important in medical training, indicating an unmet need. Nearly all respondents (59, 96.7%) found value in the ability to visualize patients' clinical findings in the XR rounding experience and 60 (98.4%) found value in the ability to visualize patient-specific imaging and test findings in an XR format. Limiting exposure to high-risk patients and care team members with this innovative format was believed to be important to 79 (96.3%) respondents at baseline and that perception was unchanged following the event. Next Steps: This solution to a long-standing dilemma, newly stressed by a unique era in medicine, was a successful collaboration using state-of-the-art XR technology. Next steps will include introducing more advanced physical exam visualization and detection and comprehensive evaluation of the patient experience, as well as expanding the international experience in a format that is scalable to other interested institutions.